HERDING BEHAVIOR OF INDONESIA INVESTOR: ROLE OF PERSONALITY TRAITS AND MOTIVATION FACTORS - Candy Candy; Indra Novita (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aimed to determine the relationship between personality traits and motivation factors that causes herding behavior among individual investors in Indonesia. Personality traits included compliant, aggressive, and detached, while motivation factors used the cognitive ability, social factors, and emotional factors. This study's research method uses an online survey by distributing questionnaires to the stock investor in Indonesia. There were 460 questionnaires collected from the distribution of 1,534 sets of the questionnaire, and there were also 52 sets of the questionnaire are incompleted—the collected sets of data analyzed by using multiple regression. This study indicates that a compliant and aggressive personality has a significant positive effect on herding behavior. Meanwhile, a detached personality has a significant negative effect on herding behavior. Apart from that, the motivational factors that comprise cognitive ability, social factors, and emotional factors also significantly affected herding behavior.